Effect of the engine calibration parameters on gasoline partially premixed combustion performance and emissions compared to conventional diesel combustion in a light-duty Euro 6 engine. (15th October 2018) - Belgiorno, Giacomo; Dimitrakopoulos, Nikolaos; Di Blasio, Gabriele; Beatrice, Carlo; Tunestål, Per; Tunér, Martin
Highlights: Optimization of calibration parameters in partially premixed combustion. Thermodynamic analysis of light duty engine operating in partially premixed mode. A 50% of NOx and soot reduction adopting gasoline partially premixed combustion. −5% of fuel consumption with partially premixed combustion compared to diesel fuel. Abstract: A design of experiments analysis was performed to investigate the effects of pilot quantity, combustion phasing and exhaust gas recirculation on performance and emissions in a gasoline partially premixed combustion to find out the optimal combination of the all varied parameters. The experimental activities were performed on a light-duty Volvo Euro 6 diesel engine. The test was performed under steady-state operating conditions, nine test points were chosen inside the operating area of the New European Driving Cycle and the Worldwide Harmonized Light vehicles Test Cycles. A fractional factorial analysis in partially premixed combustion on the single and combined effect of the main engine calibration parameters and a global comparison between partially premixed combustion and conventional diesel combustion on the engine performance and emissions adopting the optimal calibration parameters obtained from design of experiments analysis for both combustion modes analysed were presented. The purpose was to obtain the calibration parameters setting that permits to achieve high efficiency and low emissions as well. The partially premixed combustion results show the highest efficiency and lowest NOx emissions adopting a high exhaust gas recirculation rate combined with advanced combustion phasing and lower pilot quantity. Higher efficiency, up to 2.0% units, was obtained in partially premixed combustion with respect to the conventional diesel combustion due to the lower heat transfer loss. Lower soot (about two times) and NOx (about −0.5 g/kWh) levels with partially premixed combustion were obtained and compared to conventional diesel combustion at the same exhaust gas recirculation level. A reduction of about 5% of CO2 and fuel consumption with a 50% of reduction on NOx and soot simultaneously were obtained for partially premixed combustion on the New European Driving Cycle estimation results with respect to the diesel combustion. The information derived from this work are useful to develop and calibrate a light-duty engine that operate in gasoline partially premixed combustion mode achieving NOx close to the Euro 6 limit without adopting any after treatment system.